READINESS OF EDUCATIONAL INSTITUTIONS AND EDUCATION PERSONNEL (LPTK) STUDENTS IN THE UNRAM PROGRAM TO BECOME ELEMENTARY TEACHERS - Muhammad Makki; Husniati Husniati; Baiq Niswatul Khair (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2023)
The purpose of this study is to describe the readiness of higher education LPTK students in Prodi PGSD Unram to become professional SD teacher candidates in terms of knowledge, practice, and attitude, as well as to describe the dominant factors that hinder the readiness to become professional SD teacher candidates. This type of research is quantitative survey method. Instruments for collecting test data, questionnaires, and observation sheets. This study aims to obtain an overview of the characteristics of the population related to the readiness of students to become professional SD teacher candidates. The population in this research is Mataram University. The sampling technique used is area sampling. The results of this study indicate in terms of knowledge about students and how to learn the results of the analysis show an average value of 25.74 in the high category. This shows that students are ready to become SD professional teachers. While the questionnaire on the ability to carry out learning when viewed from the average value, which is 136.24 in the high category. In the aspect of perception of being an SD teacher, the average score is 103.60 with the agree category. Furthermore, on the confidence data to become a professional SD teacher, the data analysis results obtained an average of 140.04 with the agree category